0592 Hybrid Closed Loop Insulin Delivery Systems Reduce Perceived Hypoglycemia During Sleep in Adults With Long-Standing Type 1 Diabetes and Hypoglycemia Unawareness. (25th May 2022) - Matus, Austin; Malone, Susan Kohl; Flatt, Anneliese; Peleckis, Amy; Dalton-Bakes, Cornelia; Rickels, Michael; Goel, Namni
Abstract: Introduction: Sleep-associated hypoglycemia is a major concern for individuals with type 1 diabetes (T1D). Hybrid closed loop insulin delivery systems with continuous glucose monitoring (HCL-CGM) may reduce the perceived frequency, severity, and impact of sleep-associated hypoglycemia. This analysis assessed changes in perceived sleep-associated hypoglycemia in individuals with T1D at high risk for hypoglycemia after initiating HCL-CGM. Methods: Seven adults (median age=53y) with long-standing T1D (median duration=41y) and hypoglycemia unawareness participated in an ongoing 18-month clinical trial assessing effectiveness of HCL-CGM. At baseline and every 6 months thereafter, participants completed the validated Hypoglycemia Awareness Questionnaire (HypoA-Q), a 33-item tool consisting of three subscales (impaired awareness, symptom level, and symptom frequency), and 16 conceptually distinct items, including six items that relate to the frequency, severity, and impact of sleep-associated hypoglycemia, each which is scored and assessed individually. Friedman Tests assessed changes in items over the 18-month interval and Kendall's W determined effect sizes. Results: HCL-CGM significantly reduced the reported frequency of the following questions: (a) "How often you have had a hypo during your sleep?" (χ2(3)=8.4, p<0.05; moderate effect size, W=0.40) and (b) "…and were unable treat yourself when you woke up?" (χ2(3)=12.1, p<0.05; large effect size, W=0.57). HCL-CGM also reduced the reported frequency to: (c) "…and someone else gave you sugar by mouth?" (χ2(3)=7.2, p<0.07; moderate effect size, W=0.34). By contrast, HCL-CGM did not affect reported frequency to the questions: (d) "…which led to a major problem?" (p>0.05; moderate effect size, W=0.26)"; (e) "…and someone else gave you a glucagon injection?" (p>0.05; small effect size, W=0.14); and (f) "…where you stayed asleep and only later realized that you had been hypo?" (p>0.05; small effect size, W=0.19). Conclusion: HCL-CGM improved various critical aspects of perceived sleep-associated hypoglycemic events in individuals most at-risk for hypoglycemia. Our results have important implications for self-care and patient treatment in this population. Support (If Any): NIH R01DK117488 (NG), R01DK091331 (MRR), K99NR017416 (SKM), and UL1TR001878 (University of Pennsylvania Center for Human Phenomic Science); NASA NNX14AN49G and 80NSSC20K0243 (NG); Pennsylvania Department of Health SAP 4100079750 (IL).